Determinants of Exchange Rate in Nigeria: A Comparison of the Official and Parallel Market Rates - Akintunde, Yusuf Wasiu; Ebunoluwa O, Oyegoke; Jelilov, Gylych; Mary, Haruna Timipre (The Economics and Finance Letters, 2019)
The need to understand what drives exchange rates is now very crucial, an understanding of its determinants particularly in a developing nation like Nigeria would indeed aid in policy decisions of the sovereign monetary authorities. The study examines the determinants of exchange rate in Nigeria comparing the official exchange rates and the parallel market rates from the post SAP era of 1986 to 2017 using quarterly time series data. The potential determinants of the exchange rate was identified resting on existing literature viz ; GDP, inflation, interest rates, imports, oil exports, non-oil exports, and reserves. The time series properties were tested utilizing the Augmented Dickey-Fuller (ADF) unit roots test of stationarity, the variables were tested for co-integration and the Auto-regressive Distributed Lag Model (ARDL) was applied. The result suggests that GDP, inflation, interest rates non- oil exports, oil exports and reserves are the major determinants of official exchange rates in Nigeria, while inflation, Non-oil exports and GDP are the major determinants of alternate or parallel exchange rates.